Table 1_Nutritional self-management in chronic diseases: a conceptual analysis.docx - Lingzhu Zhang (12131840) (2025)
Aims This study employs conceptual analysis to clarify the core definition of nutritional self-management in chronic diseases, addressing the critical issues of ambiguous conceptualization and the lack of operational standards in current nutrition management against the backdrop of increasing chronic disease burden. The findings aim to establish a scientific clinical evaluation framework and inform evidence-based intervention strategies. Methods Walker and Avant’s concept analysis approach was used to analyze the concept of nutritional self-management in chronic diseases. A comprehensive literature search was conducted across PubMed, Web of Science, CINAHL and Embase databases, spanning from their inception to 2024. Results A total of 52 articles were included after screening. Nutritional self-management in chronic diseases was defined by six attributes: (1) Dietary management adherence. (2) Establishing collaborative partnership between patients and healthcare providers. (3) Acquisition, evaluation and utilization of healthcare resources. (4) Decision-making and action. (5) Perception and adaptation to patient role. (6) Emotional regulation and management. The antecedent variables of nutritional self-management in chronic diseases were sociodemographic factors, nutritional self-management ability, opportunities, and motivation. The consequences mainly affected the patients from three dimensions: the individual, family and society, forming a virtuous cycle of “patient benefit-family stress reduction-social efficiency improvement.” Conclusion This study systematically develops a conceptual model of nutritional self-management for chronic disease patients, grounded in classical Walker and Avant’s concept analysis. Through integrative analysis of common characteristics in chronic disease nutrition management, we propose a theoretically-grounded structured framework that establishes an essential foundation for developing standardized assessment tools and conducting clinical empirical research. While the core elements demonstrate cross-cultural applicability, their real-world implementation requires careful consideration of contextual moderating factors across different regions. We recommend future multi-center collaborative studies incorporating disease-specific characteristics to further validate the generalizability of this framework.